Identification of Proteins with Potential Osteogenic Activity Present in the Water-Soluble Matrix Proteins from Crassostrea gigas Nacre Using a Proteomic Approach - Daniel V. Oliveira; Tomé S. Silva; Odete D. Cordeiro; Sofia I. Cavaco; Dina C. Simes (The Scientific World Journal)
Nacre, when implanted in vivo in bones of dogs, sheep, mice, and humans, induces a biological response that includes integration and osteogenic activity on the host tissue that seems to be activated by a set of proteins present in the nacre water-soluble matrix (WSM). We describe here an experimental approach that can accurately identify the proteins present in the WSM of shell mollusk nacre. Four proteins (three gigasin-2 isoforms and a cystatin A2) were for the first time identified in WSM of Crassostrea gigas nacre using 2DE and LC-MS/MS for protein identification. These proteins are thought to be involved in bone remodeling processes and could be responsible for the biocompatibility shown between bone and nacre grafts. These results represent a contribution to the study of shell biomineralization process and opens new perspectives for the development of new nacre biomaterials for orthopedic applications.